The Effect of Liquidity, Solvency and Activities on The Profitability of Agricultural Sector Companies Listed on The Indonesia Stock Exchange - Hendrasari, Widya Kurnia; Warsono, Warsono; Fitriasari, Fika (Universitas Muhammadiyah Malang, 2023)
This study aims to determine the effect of liquidity, solvency, and activity on profitability in agricultural sector companies in 2012 – 2021. This type of research is survey research. The population used is all agricultural sector companies using the purposive sampling technique so that there are 6 samples of companies with a time period of 10 years so that the sample to be observed is 60. This study uses the documentation method obtained from the annual financial statements on the website (www.idx.co.id). The data analysis technique used the OLS (Ordinary Least Square) model. The results showed that liquidity, solvency, and activity simultaneously had a significant effect on profitability. Partially, liquidity, and activity have a significant effect, while solvency has no significant effect on profitability.